Towards the polymer nanocomposites based on hairy nanoparticles - Sharma, Aakash; Kruteva, Margarita (Frontiers in Physics, 2022)
Polymer nanocomposites exhibit versatility in their mechanical and structural features predominantly due to the huge surface area provided by nanoparticles. Interaction of the nanoparticles with polymer matrix selectively dictates the applications suitable for a particular polymer nanocomposite system. Novel hybrid polymer-derived materials based on polymer grafted nanoparticles (NPs) can either be mixed with the polymer matrix or self-suspended without matrix polymer. In both cases superior properties are demonstrated compared to the traditional polymer nanocomposites, most notably by (i) incorporation of NPs into polymers without “mixing problems” and (ii) a wide range of the transport phenomena (from solids to viscous fluids). Hence, hairy nanoparticle-based nanocomposites are equipped to handle specific and unique challenges in manufacturing and processing methods. It is known that the transport properties can be tuned by altering the molecular design of hairy nanoparticles (i.e., grafted polymer chemistry, NP concentrations, grafting density, and polymer molecular weight) and matrix polymer (e.g. molecular weight). In this article, we review the (i) most common methods of synthesizing hairy nanoparticle, (ii) their microscopic dynamics and structural features and (iii) some interesting applications of nanocomposite based on hairy nanoparticles. We discuss the effect of various parameters like nanoparticle size, molecular weight of the polymer etc. on the features of nanocomposites and its implications on the properties.